KINERJA KA SANCAKA KELAS EKSEKUTIF DAN KELAS BISNIS DITINJAU DARI KEPUASAN PENGGUNANYA - Ika Setiyaningsih (Universitas Muhammadiyah Surakarta, 2015)
KA Sancaka that serve Yogyakarta-Surabaya route has a very important role for the movement of people and goods between the two cities. Competition among modes of land transport and air modes also requires the ope-rator to be able to provide good performance for users KA Sancaka. For that is necessary to study how users KA Sancaka assess the performance of both the executive class or business-class. Data retrieval is based on the results of questionnaire respondents Sancaka KA users. The total number of samples of 558 respondents bottom-right on the population data of passenger volume in the first week (dated August 2 to 8, 2010) as many as 1287 passengers in business class and 687 executive class passengers. Analysis of data using IPA (Importance Performance Analysis).Results indicate that the performance variable performance Sancaka KA executive class and business class today is pretty good. Variables placed quadrant 1 need attention from PT. KAI From each of the 24 variables, 7 variables in executive class and 13 in business class variable has been in line with expectations applications of nanya. Variables in quadrant 3 can be maintained in accordance with what has been done in the current conditions. Variables in quadrant 4 although considered important by the user can still be tailored to the user's wishes.